2011
DOI: 10.1111/j.1540-8167.2011.02128.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Complex Fractionated Electrograms (CFE) and Dominant Frequency (DF) Sites and Prospective Assessment of Adding DF-Guided Ablation to Pulmonary Vein Isolation in Persistent Atrial Fibrillation (AF)

Abstract: DF and CFE regions overlap only about 50%. AF termination retrospectively occurred on overlapping CFE/DF sites where DF was above the mean. However, prospective ablation of DF sites plus PVAI resulted in low AF termination rates, and did not improve 1 year success over PVAI alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 27 publications
4
69
1
Order By: Relevance
“…31 As observed here, regions harboring CFAE have also previously been noted to be more extensive than those with high DF. 31 Previous investigators have noted that fractionated electrograms tend to occur adjacent to high-DF areas rather than directly superimposed on them.…”
Section: Catheter Contact and Spectral Analysis Parameterssupporting
confidence: 70%
See 1 more Smart Citation
“…31 As observed here, regions harboring CFAE have also previously been noted to be more extensive than those with high DF. 31 Previous investigators have noted that fractionated electrograms tend to occur adjacent to high-DF areas rather than directly superimposed on them.…”
Section: Catheter Contact and Spectral Analysis Parameterssupporting
confidence: 70%
“…31 As observed here, regions harboring CFAE have also previously been noted to be more extensive than those with high DF. 31 Previous investigators have noted that fractionated electrograms tend to occur adjacent to high-DF areas rather than directly superimposed on them. 32 The latter is the probable explanation for high-DF points not being significantly more likely to be high-grade CFAE points in this study.…”
Section: Catheter Contact and Spectral Analysis Parameterssupporting
confidence: 70%
“…21 Others have proposed targeting overlapping ; however, the role of dominant frequency in AF ablation remains unsettled. 23 In one large retrospective study of hundreds of EGMs, those exhibiting a high percentage of CEA were most likely to be associated with AF termination or increases in AFCL. 7 Further study in human AF has shown that CEA is highly prevalent in antral sites in paroxysmal AF, correlating with an increased efficacy of PVI alone in paroxysmal subjects.…”
Section: Selective Versus Generalized Cfae Regionsmentioning
confidence: 99%
“…The study lacked a control group without DF ablation, and the results achieved with their combined technique were not superior to those widely reported using CPVI alone. [27][28][29] Among patients with persistent AF, Verma et al 27 combined DF ablation with CPVI. Despite ablating all LA sites with a DF greater than the mean, there was minimal impact on AF cycle length, and long-term outcomes were not different from those in a control group that underwent CPVI alone.…”
Section: Is a Frequency-map-guided Ablation Strategy Rational?mentioning
confidence: 99%